The Impact of Aligning Kolb’s Experiential Learning Theory with a Comprehensive Teacher Education Model on Preservice Teachers’ Attitudes and Teaching Practice - Mechouat, Karima (European Scientific Journal, ESJ, 2024)
Since its inception, experiential learning has been a foundational tenant of teacher education. However, it is questionable as to the level of authentic experiential learning practices that are actually taking place. This paper presents one approach to addressing this situation, based on Kolb’s Experiential Learning Theory Model. As such, this exploratory manuscript examines Kolb’s Experiential Learning Cycle (ELC) further, and considers the implications for Experiential Learning Theory (ELT) in teacher education. A description of teacher education program in the CRMEF (Centre Régional des Métiers de l’Education et de la Formation) is provided, then results from a quantitative and qualitative survey are triangulated with teacher trainees’ reflection journals to evaluate the training program in terms of the teacher trainees’ developing confidence and competence in teaching. Therefore, the present research will explore the implementation of this approach for teacher education in the CRMEF. Results indicate that the great majority of the participants have developed both their confidence to teach using this approach, thus, changing their perceptions and attitudes towards the teaching of English language. Specific learning experiences that help affect their sense of confidence and competence in teaching include in-person, experiential and hands-on approaches to learning relevant skills and knowledge, which confirms the importance of using Kolb’s ELC as the basis for teacher education program. The study recommends that teacher educators enhance their programs by providing instruction to pre-service teachers in authentic experiential learning pedagogy. Therefore, a comprehensive model for teacher education is suggested to demonstrate the role of experiential learning.